Filipino Muslims in Kalibo, Aklan self-concept, perceived prejudice after the 9/11 attack and their level of religiousity. - Idorot, Rena Q.; Sapio, Jed P.
This is a descriptive study which sought to determine the following : (1) the self-concept of Filipino Muslims (2) the perceived prejudice after the 9/11 attack
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines, Visayas, Miagao, Iloilo
Keywords: Filipino Muslims--Kalibo, Aklan